Lifelong Learning in the Global Knowledge Economy : Challenges for Developing Countries - World Bank (Washington, DC, 2013)
Consideration of lifelong learning extends the World Bank's traditional approach to education, in which subsectors are looked at in isolation. Three years ago, when he articulated the Comprehensive Development Framework, World Bank President James Wolfensohn referred explicitly to lifelong learning as a component of what education means for poverty alleviation In 1995 "Priorities and Strategies for Education" (report no. 14948) emphasized the need to look at the education system in a more holistic manner. The 1999 "Education Sector Strategy"(report no. 19631) discussed the role of new technologies. The World Bank has just completed important new policy work on higher education reforms as well as a vision paper on the role of science and technology. The current report is the Bank's first attempt to lay out an analytical framework for understanding the challenges of developing a lifelong learning system. While the World Bank's involvement in lifelong education is still at the conceptual stage, two new projects-in Romania and Chile-have already been prepared to address the need for continuing education and lifelong learning. In the years to come more analytical work on lifelong learning is expected, and the policy dialogue in education will touch more and more on lifelong learning issues. The Bank's lending program will involve operations to support countries' efforts to transform their education systems to reflect a lifelong learning approach. This report provides a departure point for these continuing discussions, providing a conceptual framework for education-related lending activities reflecting the latest knowledge and successful practices of planning and implementing education for lifelong learning. It encourages countries to look beyond traditional approaches to education and training and to engage in a policy dialogue on the pedagogical and economic consequence of lifelong learning.